Clinical features and risk factors for mortality in patients with Klebsiella pneumoniae bloodstream infections - Panpan Xu; Xijiang Zhang; Qingqing Chen; Qin Si; Xinhua Luo; Chuming Zhang; Zongguang He; Ronghai Lin; Cheng Zheng (Journal of Infection in Developing Countries)
Introduction: Concern about Klebsiella pneumoniae (K. pneumoniae) bloodstream infections (KP-BSIs) is widespread because of their high incidence and lethality. The aim of this study was to investigate the clinical features of, and risk factors for mortality caused by KP-BSIs.